A Case Report Illustrating the Postoperative Course of Descemetorhexis without Endothelial Keratoplasty with Topical Netarsudil Therapy - Pimpiroon Ploysangam; Sangita P. Patel (Case Reports in Ophthalmological Medicine)
Fuchs endothelial corneal dystrophy (FECD) is the most common indication for corneal transplantation in the United States. Recently, descemetorhexis without endothelial keratoplasty (DWEK) or Descemet’s stripping only (DSO) has become an attractive alternative to corneal transplantation for these patients. DSO circumvents the challenges associated with cadaveric donor corneal transplantation by tapping into the potential of the patient’s own corneal endothelium to repair defects. Outcomes have been variable with emerging knowledge on predictive factors for success. Our case describes a 51-year-old patient with visually significant confluent central guttae from FECD who underwent a successful DSO with immediate post-operative use of the Rho-associated protein kinase (ROCK) inhibitor (netarsudil). We report the preoperative and post-operative slit lamp images, specular microscopy data, and corneal topography, thickness, and densitometry data. These represent a unique data set for this new surgical treatment option for FECD. Despite a small descemetorhexis, we show the improvement in corneal thickness and opacity extends beyond the boundaries of the descemetorhexis. Early initiation of a ROCK inhibitor was a successful treatment for this patient.